2021
DOI: 10.1108/jocm-01-2021-0015
|View full text |Cite
|
Sign up to set email alerts
|

Boosters of satisfaction, performance and employee loyalty: application to a recruitment and outsourcing information technology organization

Abstract: PurposeThis study applies an Employee Satisfaction Index (ESI) model to quantify the level of job satisfaction and explores the factors that influence employee satisfaction, performance and loyalty to an information technology recruitment and outsourcing organization in Portugal.Design/methodology/approachAs an instrument of data collection, questionnaire was applied to the company's employees, which was divided into two parts: the first part consisted of a previous questionnaire, with questions related to soc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
17
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(22 citation statements)
references
References 30 publications
3
17
0
2
Order By: Relevance
“…Companies usually take various team stabilization measures to improve organizational efficiency and morale. Previously, managers usually increased employee loyalty by offering promotions, increasing salaries, and benefits ( Veloso et al, 2021 ). The results of this study show that OT and OI have significant positive effects on EL.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Companies usually take various team stabilization measures to improve organizational efficiency and morale. Previously, managers usually increased employee loyalty by offering promotions, increasing salaries, and benefits ( Veloso et al, 2021 ). The results of this study show that OT and OI have significant positive effects on EL.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, in modern enterprise management, how to retain talents and cultivate employee loyalty has been the focus of researchers and managers. EL is defined as an individual’s identification with the core values philosophy of the organization, which embodies the psychological state of the relationship between the employee and the firm, and is willing to stay in the firm and make a great effort ( Meyer and Allen, 1991 ; Veloso et al, 2021 ). EL is a concentrated manifestation of psychology and emotion ( Dhir et al, 2020 ).…”
Section: Theoretical Background and Hypothesesmentioning
confidence: 99%
See 1 more Smart Citation
“…Some studies have explored the antecedent variables of organizational loyalty ( Matzler and Renzl, 2006 ). Veloso et al (2021) revealed that employee satisfaction contributes significantly to employee organizational loyalty and contextual performance. Nguyen (2021) found the factors affecting the employees’ loyalty in private joint-stock commercial banks in Mekong Delta.…”
Section: Literature Review and Hypothesesmentioning
confidence: 99%
“…A research paper by Veloso et al (2021) measures employee satisfaction and the elements that lead to or hinder it – namely, a person's performance, loyalty to the company, and feelings around professional satisfaction. To gather data for the study, questionnaires were completed by employees at an information technology (IT) recruitment and outsourcing company based in Lisbon, Portugal.…”
mentioning
confidence: 99%